Evaluasi Penggunaan Antibiotik pada Pasien Faringitis Di Suatu Rumah Sakit Di Kota Bandung - Ida Lisni (JURNAL FARMASI GALENIKA, 2015)
Acute respiratory infections (ARI) is a very serious health problem in the world or in Indonesia. Period prevalence of ARI in Indonesia according Riskesdas 2013 amounted to 25.0%. Respiratory tract infections such as pharyngitis represent the vast majority of cases. Pharyngitis is largely caused by the bacterium Streptococcus group A Î²-haemolytic. One of the main drug is an antibiotic to treat pharyngitis. Improper use of antibiotics in the treatment of pharyngitis can lead to resistance and side effects, it is necessary to drugs use evaluate as a form of quality assurance of drug use to assess the suitability of the use of antibiotics in the treatment of pharyngitis. Research conducted an observational study with descriptive data presentation and data collection retrospectively. Based on the results of research in the period January to April 2015 obtained 56 patients studied. Patients with pharyngitis is pediatric (53.57%) and 46.43% is adult patients. All patients studied using antibiotic therapy. Antibiotics are widely used cephalosporins (89.29%), with sefiksim (60.71%). Results of the qualittive analysis known that patients received appropriate indication of antibiotic is 100%, appropriate doses of 96.49%, duration of therapy appropriate for 87.72%, the use of antibiotic combination that has a synergistic effect in 1(one) patient. There is no duplication, but there are 14 cases that have the potential occur drug interactions.